The Legal Protection for Land Rights Holders Due to Loss of Data - Alam, Bahrul (Jurnal Konstatering, 2022)
In its history before the enactment of the UUPA there was a dualism of Agrarian Law in Indonesia. This dualism in agrarian law is more detrimental to indigenous groups, because customary law governing lands with customary rights is an unwritten law, while on the other hand land with western rights is regulated by written western law. Registration for lands subject to western law aims to provide legal certainty guarantees known as Rechts Cadaster or Legal Cadaster.The formulation of the problem in this study are: 1)legal protection for land rights holders due to loss of data at the Kendari City Land Office, 2) the impact of loss of land records on community land rights in Kendari City, 3) legal aspects of legal protection of land rights resulting from data recovery.The method used by researchers isnormative legal approachandspecifications in this study are included in the analytical descriptive.The sources and types of data in this study are primary data obtained from field studies by interviewingBPN in Kendari City.And secondary data obtained from literature studies. Based on the results of research that legal protectionagainst land rights holders due to loss of data at the land office namely1)BPN only provides legal protection to certificates of land rights whose archives have been restored; 2) The purpose of data recovery is to provide legal protection for land rights whose records have been lost/destroyed. BPN recovers data and re-approves land certificates and books as well as measurement papers based on Article 18 Perkaban Number 6 of 2010. The impact of the loss of land records on community land rights in Kendari City is 1) the loss/destroy of land records can weaken the strength of evidence of a certificate as evidence of land rights; 2) the impact of the destruction of land records results in certificates of land rights whose data cannot be used as evidence before being recovered before committing legal acts; 3) loss or destruction of land records does not necessarily eliminate/remove the right to the land in question. Legal aspects of the legal protection of land rights resulting from data recovery are 1) Substantial Aspects, 2) Structural Aspects, 3) Cultural Aspects.Keywords: Land; Protection; Rights.